Modelo de otimização para seleção de árvores matrizes de Eucalyptus grandis - Barreiros, Ricardo Marques [UNESP]; Garcia, José Nivaldo; Caixeta Filho, José Vicente; Sansigolo, Cláudio Angeli [UNESP] (My University, 2002)
Individual data of basic density and volume of wood, pulp kappa number, soluble lignin, cost of pulping process as well as gravimetric gross yield of pulping process were used from 64 trees of Eucalyptus grandis W. Hill ex Maiden from a commercial population at Lençóis Paulista, SP. The Eucalyptus grandis's seeds were originally from a Seed Production Area (SPA) of Duratex S/A at Botucatu, SP. Obtained data were quantified considering objective of maximization no-bleaching pulp and volume and mass wood restriction, mass of residual and soluble lignin, planted area and pulping process cost. it has also been aimed a selection method for matrix trees through mathematical programming techniques. Obtained strategy maximized the economical result, selected matrix trees and followed all limits of technological and organizing productivities imposed by the company. It also aimed the production of no-bleaching pulp within the planned time.
Optimization model for selection of Eucalyptus grandis matrix trees
Keywords: Eucalyptus grandis; Linear programming; Modelling; Pulping; Selection; Cost effectiveness; Density (specific gravity); Economic and social effects; Lignin; Seed; Unbleached pulp; Wood; Soluble lignins; Forestry; Eucalyptus Grandis; Kappa Number; Lignins; Linear Programing; Seeds; Unbleached Pulps